Inflammatory Related Cardiovascular Diseases: From Molecular Mechanisms to Therapeutic Targets - Sardu, Celestino; Paolisso, Giuseppe; Marfella, Raffaele (Current pharmaceutical design, 2020)
Inflammation is a pathogenic response to multiple factors, that causes over-activation of different molecules and pro-inflammatory cellular lines. Different behavioral factors and risk factors might enhance the inflammatory stress, and this might cause cardiovascular disease (CVD). CVD is the world's leading cause of morbidity and mortality, and it is represented by hypertension, coronary heart disease, cerebrovascular disease, peripheral vascular disease, heart failure, rheumatic heart disease, congenital heart disease and cardiomyopathies. In this context, inflammation is both a cause and an aggravating factor in CVD, as well as a mediator of its worst prognostic. The mechanisms that link inflammation to CVD are multiple, complex and multi-factorial. To date, the role of inflammation in the genesis and progression of CVD has been extensively analyzed in recent studies. However, in the last decades, new biomarkers are joining the already known inflammatory biomarkers, such as Creactive protein, interleukins, tumor necrosis factor alpha and nitrotyrosine. Among these new biomarkers, we have to report sirtuins, microRNAs, ST2 protein, apolipoprotein E protein, adiponectin, and others. These biomarkers are preferentially expressed locally in the target tissue of inflammation, but also released in peripheral blood and then used as diagnostic and prognostic biomarkers. Indeed, these biomarkers might also predict future adverse cardiovascular events and worse prognosis in patients with CVD. Furthermore, these new inflammatory biomarkers can also be analyzed to evaluate therapeutic efficacy in patients with CVD. Furthermore, this might open up new fields and interesting research concerning the link between inflammation and CVD.